(untitled) (TAJ: Journal of Teachers Association, 2020)
Background & objective: Childhood underweight or overweight prevention efforts are unlikely to be successful without a better understanding of how parents perceive the problem of underweight or overweight in their children. This study was carried out with the objective of comparing perceptions (parents’ and self) of the nutritional status with the actual nutritional status measured by BMI. Materials & Methods: This Cross-sectional study was carried out in the Department of Pediatrics, Sir Salimullah Medical College, Mitford hospital, Dhaka over a period of 12 months, from July 2008 to June 2009. Three schools in Dhaka Metropolitan city were selected by multistage sampling (lottery method). A self– administered parents’ questionnaire was filled by parents. Then the student’s nutritional status was defined according to age and gender specific body mass index percentile from CDC-2000 reference as underweight (< 5th percentile), normal (5th - 85th percentile), overweight (85th - <95th percentile),) and obese (95th percentile and above). Chi-square test was used for testing statistical significance. Results: This study found the double burden of under nutrition and obesity in school children of Dhaka city (41.4% as underweight, 48.5% as normal weight, 5.6% as overweight, and 4.5% as obese). Obesity (6% vs. 2.2%) and overweight (6.6% vs. 2.2%) was higher in boys than girls, although underweight was almost similar (42% vs. 41%) in boys and girls. Majority of children (602 among 1026) failed to perceive their actual body image (58.7%) and almost half of the parents (371 among 772) also failed to perceive the actual body image of their children (48.1%). Among underweight, overweight and obese children 87.3% had incorrect self-perception of nutritional status. 75% of parents’ perception was incorrect in the above mentioned group. Conclusion: Underweight and obese school children had the most incorrect self-perception. Similarly parents of the underweight and obese children group had the most incorrect parents’ perception. These are the alarming situation and demand our immediate attention. TAJ 2019; 32(2): 7-13